Incorporation of Al3+ Sites on Brønsted Acid Metal–Organic Frameworks for Glucose‐to‐Hydroxylmethylfurfural Transformation. Issue 22 (18th March 2021) - Tangsermvit, Vitsarut; Pila, Taweesak; Boekfa, Bundet; Somjit, Vetiga; Klysubun, Wantana; Limtrakul, Jumras; Horike, Satoshi; Kongpatpanich, Kanokwan
Abstract: 5‐hydroxylmethylfurfural (HMF) is a bio‐based chemical that can be prepared from natural abundant glucose by using combined Brønsted–Lewis acid catalysts. In this work, Al 3+ catalytic site has been grafted on Brønsted metal–organic frameworks (MOFs) to enhance Brønsted–Lewis acidity of MOF catalysts for a one‐pot glucose‐to‐HMF transformation. The uniform porous structure of zirconium‐based MOFs allows the optimization of both acid strength and density of acid sites in MOF‐based catalysts by incorporating the desired amount of Al 3+ catalytic sites at the organic linker. Al 3+ sites generated via a post‐synthetic modification act as Lewis acid sites located adjacent to the Brønsted sulfonated sites of MOF structure. The local structure of the Al 3+ sites incorporated in MOFs has been elucidated by X‐ray absorption near‐edge structure (XANES) combined with density functional theory (DFT) calculations. The cooperative effect from Brønsted and Lewis acids located in close proximity and the high acid density is demonstrated as an important factor to achieve high yield of HMF. Abstract : Lewis Al 3+ sites have been incorporated into Brønsted sulfonated MOFs to promote glucose conversion to 5‐hydroxylmethylfurfural, which is a value‐added chemical obtained from sugars. The local structure of acid sites has been elucidated by X‐ray absorption near‐edge structure (XANES) combined with density functional theory calculations.